TRENDS IN INTRODUCTION OF SMART CITY TECHNOLOGIES IN URBAN COMMUNITY DEVELOPMENT STRATEGY (INNOVATIVE ECONOMY, 2021)
Horshkov M.А., Lozovskyi О.М. TRENDS IN INTRODUCTION OF SMART CITY TECHNOLOGIES IN URBAN COMMUNITY DEVELOPMENT STRATEGYPurpose. The purpose of the article is to analysis of trends and formation of recommendations for the introduction of smart city technologies in the development strategy of the urban community.Methodology of research. The research methodology contains the following general scientific methods, namely: bibliographic – for the analysis and systematization of scientific works on the development of "smart" cities, modelling of their technological and information structures; historical and practical – to study the practical experience of introducing intellectual elements in the urban space; comparative – to determine the priorities of the components of the "smart city" model; abstract and logical – in forming conclusions and formulating recommendations.Findings. It is determined that the European model of smart city development provides for the introduction of such components as smart - economy, mobility, ecological approach to environmental protection; digital technologies; development of information, digital and general culture of residents; smart lifestyle; e-government. The world tendencies and Ukrainian practices of introduction of smart elements for digitalization of management of infrastructure of the city are analysed.It is determined that the technological solutions of a smart city are developed on the basis of Internet of Things technologies, active use of feedback principles, formation of data transmission infrastructure, data collection, processing and analysis systems. It is revealed that the introduction of smart technologies is carried out in fragments both in Ukraine and in the world. It is analysed that the development strategies of Ukrainian cities do not contain separate sections on the introduction of smart technologies. Ukrainian cities lag far behind in the pace of innovation and do not have separate strategies for the development of a smart city. It is proved that all stakeholders should have information on the formation of the city's development strategy and, in particular, its smart technologies, understands their level of responsibility and participation in decision-making mechanisms and implementation of the introduced technologies.Originality. The model of a smart city has been improved, taking into account trends in the development of smart cities and identifying priority areas for the development of smart technologies in the management of infrastructure and urban information environment. The information environment involves the use of a multi-loop information system to support the life of the city in various areas. Such a system contains the necessary functionality, as well as special emotional and motivating contours to increase the activity of citizens, ensure transparency of decision-making by city leaders and more. Practical value. The formed recommendations can be used by project groups of city councils for improvement of strategies of development of cities and development of scenarios of introduction of elements of system of the smart city.Key words: smart city, digital ecosystem, digital information environment, digital city development strategy, digital interaction services.
Keywords: Key words; smart city; digital ecosystem; digital information environment; digital city development strategy; digital interaction services